TEACHER FEEDBACK AND STUDENT RESPONSES: CLASSROOM DISCOURSE OF READING COMPREHENSION - Umamah, Umamah (Annual International Conferences on Language, Literature, and Media, 2023)
Reading comprehension is an interactive process between the reader and the text in which the reader must match the text's clues to their prior knowledge. It means that the comprehension of a reading text is influenced by the reader's prior understanding of it. The provision of teacher feedback on the reading process has been beneficial. However, the student’s reading comprehension may vary depending on the feedback mechanisms used. This study discusses the classroom discourse involving teacher feedback and student responses. The research questions cover how teachers serve feedback on the students' reading comprehension skills and how the students respond. Therefore, this study aims to see how the teacher’s feedback expectations affected student’s reading comprehension. Using a qualitative approach with basic interpretive design, this research looks at the reading comprehension abilities of seventh graders in a distant junior high school in Pamekasan, East Java. The researcher used observation and interviews as research tools. It was discovered that the student’s reading comprehension did not change significantly due to the comments. In other words, direct and indirect feedback has the same effect on the student’s reading comprehension. In sum, it is clear that the feedback can positively affect the students' reading and is inextricably linked with how the teacher gave it to them.